Expansion of Interleukin‐22– and Granulocyte–Macrophage Colony‐Stimulating Factor–Expressing, but Not Interleukin‐17A–Expressing, Group 3 Innate Lymphoid Cells in the Inflamed Joints of Patients With Spondyloarthritis. Issue 3 (15th January 2019) - Blijdorp, Iris C. J.; Menegatti, Silvia; van Mens, Leonike J. J.; van de Sande, Marleen G. H.; Chen, Sijia; Hreggvidsdottir, Hulda S.; Noordenbos, Troy; Latuhihin, Talia E.; Bernink, Jochem H.; Spits, Hergen; Rogge, Lars; Baeten, Dominique L. P.; et al.
Abstract : Objective: Clinical trials of the anti–interleukin‐17A (anti–IL‐17A) antibody secukinumab have demonstrated a crucial role of the cytokine IL‐17A in the pathogenesis of spondyloarthritis (SpA); however, its cellular source in this condition remains a matter of controversy. Group 3 innate lymphoid cells (ILC3s) have been recently identified as potent producers of proinflammatory cytokines, including IL‐17A and IL‐22, in a number of different tissues. This study was undertaken to characterize the presence and composition of ILCs, and investigate whether these cells are an important source of IL‐17A, in the synovial tissue (ST) of patients with SpA. Methods: Matched ST, synovial fluid, and peripheral blood (PB) samples were obtained from SpA patients with actively inflamed knee joints. ILC subsets were characterized by flow cytometry. Gene expression analysis at the single‐cell level was performed directly ex vivo and after in vitro activation. An IL‐17A enzyme‐linked immunospot assay was used to detect IL‐17A–secreting cells. Results: ILCs, and particularly NKp44+ ILC3s, were expanded in inflamed arthritic joints. Single‐cell expression analysis demonstrated that ST ILCs were clearly distinguishable from ST T cells and from their PB counterparts. Expression of the Th17 signature transcripts RORC, AHR, and IL23R was detected in a large proportion of ST ILC3s. These cells were capable of inducing expression of IL22 and CSF2, but not IL17A, in response to in vitro restimulation. Conclusion: Our findings demonstrate that absolute and relative numbers of ILC3s are enriched in the synovial joints of patients with SpA. However, these cells are not a significant source of IL‐17A in this disease.